On the Cauchy problem of compressible Micropolar fluids subjected to Hall current - Mingyu Zhang (AIMS Mathematics)
In this paper, the large-time behavior of global strong solutions is justified for the three dimensional compressible micropolar fluids subjected to Hall current. Both the global existence and the optimal decay rates of strong solutions are obtained when the smooth initial data are sufficiently close to the non-vacuum equilibrium in $ H^1 $. In addition, the vanishing limit of the Hall coefficient is also justified.